Hydrogen bonding analysis in amorphous hydrogenated carbon by a combination of infrared absorption and thermal effusion experiments - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1996)
A detailed analysis of the bonding configurations of hydrogen in amorphous carbon has been performed by measuring infrared (IR) absorption spectra and mass separated thermal effusion transients on a series of a-C:H samples deposited under self bias potentials of the substrate electrode between 0 and -1000 V. The C-H stretching as well as the bending modes of the IR absorption spectra were analysed quantitatively using IR absorption cross-sections of organic molecules for the various vibrational modes. Thermal effusion from the same samples was monitored with a quadrupole mass analyser recording eighteen relevant masses between 1 and 44 amu simultaneously and comparing the observed fragmentation patterns quantitatively with those of H2, CH4, C2H4, C2H6, C3H6 and C3H8 as calibration gases.
UnivIS-Import:2015-04-14:Pub.1996.nat.dphy.IAP.exphys.hydrog